Analytical expression between the impact damping ratio and the coefficient of restitution in the non-linear viscoelastic model of structural pounding. - Jankowski, Robert (Earthquake engineering & structural dynamics.)
Earthquake-induced structural pounding has been recently intensively studied with the help of different models of impact force. It has been verified through comparisons, that the non-linear viscoelastic model may be considered somewhat the most accurate one among them. The aim of this short paper is to derive an approximating formula relating the impact damping ratio, as a parameter of the model mentioned, with a more widely used coefficient of restitution. The accuracy of the derived analytical formulation has been confirmed through the comparison with the results of numerical simulations.